Skeletal Muscle Mass Predicts SmO2 and Physical Performance in Adolescent Badminton Athletes Using NIRS - Nida Farida; Jajat Darajat Kusumah Negara; Agus Gumilar (Universitas Negeri Semarang, 2026)
Near-Infrared Spectroscopy (NIRS) allows real-time assessment of muscle oxygenation via muscle oxygen saturation (SmO₂). This study investigated how skeletal muscle mass (SMM) influences the SmO₂ ratio and physical performance in adolescent badminton players. Using a quasi-experimental, one-time case study design, ten adolescent athletes from PB Mutiara Cardinal Bandung were selected by purposive sampling. SMM was measured with a Tanita Body Composition Analyzer, SmO₂ ratio recorded by a NIRS-based Moxy Monitor, and aerobic capacity (VO₂Max) estimated through the Bleep Test. Data underwent descriptive analysis, Shapiro–Wilk normality testing, linearity assessment, and simple linear regression. Results indicated a positive association between SMM and SmO₂ ratio (R = 0.625; R² = 0.390; Sig = 0.053), with SMM accounting for 39.0% of SmO₂ ratio variance, though this relationship did not reach statistical significance. Conversely, SMM showed a significant positive effect on physical performance (R = 0.709; R² = 0.503; Sig = 0.022), explaining 50.3% of VO₂Max variance. These results imply that while greater skeletal muscle mass predicts better aerobic performance in adolescent badminton athletes, it is not the primary determinant of SmO₂ ratio.